Civil Servant Performance Development Policy in the Regional Government of Bone Regency - Hasnawati Hasnawati; A Indrawati; Zainuddin Zainuddin; Muslimin Muslimin; Mohamad Pahrun; M. Awaluddin (Jurnal Office, 2021)
Globalization poses positive impacts such as advances in science and technology, facilitating the flow of information, communication, and distribution of goods and services. The negative impact of globalization in the form of a threat to the nation's culture, the loss of national identity, the dissolution of national borders, and the threat of other organizations. The purpose of this study is to find out how the performance of State Civil Apparatus, organizational culture concept framework, and efforts to improve the performance of Civil State Apparatus. The issue of Civil Servant performance will be accomplished and fulfilled if several factors influence it. One of the factors in question is organizational culture. The type of research is qualitative, where the data collection techniques are observation, interviews and documentation. Data analysis techniques were carried out by means of data reduction, data presentation and conclusions. Efforts to maintain the positive atmosphere of organizational culture will be able to improve employee performance, in other words the better the organizational culture the higher the high level of performance, otherwise the worse the existing organizational culture the lower level of employee performance becomes low.